Cumulative incidence and mortality of infective endocarditis in Siriraj hospital-Thailand: A 10-year retrospective study - Taksaon Angsutararux (2020)
© 2019 The Author(s). Background: To investigate the cumulative incidence of and factors associated with mortality among patients with infective endocarditis (IE) at Thailand's largest national tertiary referral center. Methods: Medical charts of adult patients diagnosed with IE by Duke criteria at Siriraj Hospital during January 2005 to May 2015 were retrospectively reviewed. Results: Of 380 patients, 66.3% had definite IE, and 81.3% had native valve IE (NVE). Cumulative IE incidence was 5.67/1000 admissions. The most common pathogens were viridans group streptococci (VGS) (39.7%), methicillin-sensitive Staphylococcus aureus (MSSA) (13.1%), and beta-hemolytic streptococci (11.5%) in NVE; and, MSSA (20.3%), VGS (20.3%), and Enterococcus spp. (16.9%) in prosthetic valve (PVE) or device-related IE (DRIE). Overall in-hospital mortality was 18.4%. Mortality was significantly higher in PVE/DRIE than in NVE (26.8% vs. 16.5%, p = 0.047). End-stage renal disease (ESRD) (aOR: 9.43, 95% CI: 2.36-37.70), diabetes mellitus (DM) (aOR: 2.81, 95% CI: 1.06-7.49), neurological complication (aOR: 14.16, 95% CI: 5.11-39.22), congestive heart failure (aOR: 4.32, 95% CI: 1.91-9.75), hospital-acquired infection (aOR: 3.78, 95% CI: 1.66-8.57), renal complication (aOR: 3.12, 95%CI: 1.32-7.37), and other complication during admission (aOR: 3.28, 95% CI: 1.41-7.61) were independently associated with mortality. Conclusions: The incidence of IE, and the mortality rate among those diagnosed with IE are both increasing in Thailand - particularly among those with PVE or DRIE. End-stage renal disease, diabetes mellitus, and development of IE-related complications during admission were found to be independent predictors of mortality.